PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN INTELEKTUAL TERHADAP PERILAKU ETIS MAHASISWA AKUNTANSI DALAM PRAKTIK PELAPORAN LAPORAN KEUANGAN - Kezia Adinda; Abdul Rohman (Diponegoro Journal of Accounting, 2015)
The aim of this study was to obtain empirical evidence about the influence of emotional intelligence and intellectual intelligence to ethical behavior accounting students in financial reporting practices.The sample in this study were taken using purposive sampling method of data collection with the criteria of the respondents had taken courses in Management Accounting, Auditing Accounting I and Practicum Accounting. This study uses S1 Accounting student in Diponegoro University with a total population of 254 people. While samples taken sebanayak 80 respondents. The data obtained were then analyzed using descriptive statistical analysis of technical, test data quality, classic assumption test, and multiple linear analysis.The results of this study indicate that emotional intelligence and intellectual positive effect on ethical behavior in the practice of accounting students reporting financial statements.